COPD profiles and treatable traits using minimal resources: identification, decision tree and stability over time - Marques, Alda (2022)
Background and objective: Profiles of people with chronic obstructive pulmonary disease (COPD) often do not describe treatable traits, lack validation and/or their stability over time is unknown. We aimed to identify COPD profiles and their treatable traits based on simple and meaningful measures; to develop and validate a decision tree and to explore profile stability over time. Methods: An observational, prospective study was conducted. Clinical characteristics, lung function, symptoms, impact of the disease (COPD Assessment Test—CAT), health-related quality of life, physical activity, lower-limb muscle strength and functional status were collected cross-sectionally and a subsample was followed-up monthly over six months. A principal component analysis and a clustering procedure with k-medoids were applied to identify profiles. A decision tree was developed and validated cross-sectionally. Stability was explored over time with the ratio between the number of timepoints that a participant was classified in the same profile and the total number of timepoints (i.e., 6). Results: 352 people with COPD (67.4±9.9 years; 78.1% male; FEV1=56.2±20.6% predicted) participated and 90 (67.6±8.9 years; 85.6% male; FEV1=52.1±19.9% predicted) were followed-up. Four profiles were identified with distinct treatable traits. The decision tree included CAT (<18 or≥18 points); age (<65 or≥65 years) and FEV1 (<48 or≥48% predicted) and had an agreement of 71.7% (Cohen’s Kappa=0.62, p<0.001) with the actual profiles. 48.9% of participants remained in the same profile whilst 51.1% moved between two (47.8%) or three (3.3%) profiles over time. Overall stability was 86.8±15%. Conclusion: Four profiles and treatable traits were identified with simple and meaningful measures possibly available in low-resource settings. A decision tree with three commonly used variables in the routine assessment of people with COPD is now available for quick allocation to the identified profiles in clinical practice. Profiles and treatable traits may change over time in people with COPD hence, regular assessments to deliver goal-targeted personalised treatments are needed.